Identification of hypoxanthine as a urine marker for non-Hodgkin lymphoma by low-mass-ion profiling - Park Sohee; Park Weon-Seo; Ahn Sun-A; Kim Kyung-Hee; Jang Sang-Geun; Kong Sun-Young; Yoo Byong; Yun Tak; Eom Hyeon-Seok (BMC Cancer, 2010)
Abstract Background Non-Hodgkin lymphoma (NHL) is a hematologic malignancy for which good diagnostic markers are lacking. Despite continued improvement in our understanding of NHL, efforts to identify diagnostic markers have yielded dismal results. Here, we translated low-mass-ion information in urine samples from patients with NHL into a diagnostic marker. Methods To minimize experimental error, we tested variable parameters before MALDI-TOF analysis of low-mass ions in urine. Urine from 30 controls and 30 NHL patients was analyzed as a training set for NHL prediction. All individual peak areas were normalized to total area up to 1000 m/z. The training set analysis was repeated four times. Low-mass peaks that were not affected by changes in experimental conditions were collected using MarkerView™ software. Human Metabolome Database (HMDB) searches and ESI LC-MS/MS analyses were used to identify low-mass ions that exhibited differential patterns in control and NHL urines. Identified low-mass ions were validated in a blinded fashion in 95 controls and 66 NHL urines to determine their ability to discriminate NHL patients from controls. Results The 30 highest-ranking low-mass-ion peaks were selected from the 60-urine training set, and three low-mass-ion peaks with high intensity were selected for identification. Of these, a 137.08-m/z ion showed lower mass-peak intensity in urines of NHL patients, a result that was validated in a 161-urine blind validation set (95 controls and 66 NHL urines). The 130.08-m/z ion was identified from HMDB searches and ESI LC-MS/MS analyses as hypoxanthine (HX). The HX concentration in urines of NHL patients was significantly decreased (P < 0.001) and was correlated with the mass-peak area of the 137.08-m/z ion. At an HX concentration cutoff of 17.4 μM, sensitivity and specificity were 79.2% and 78.4%, respectively. Conclusions The present study represents a good example of low-mass-ion profiling in the setting of disease screening using urine. This technique can be a powerful non-invasive diagnostic tool with high sensitivity and specificity for NHL screening. Furthermore, HX identified in the study may be a useful single urine marker for NHL screening.